Desenvolvimento de um compósito de resíduo de poliuretano e casca de arroz - Oliveira, Cássio Denis de (2019)
Composites made from renewable sources are replacing commonly used materials in various industrial segments, fully meeting their functional and aesthetic requirements demanded by the products. Focusing on techniques, processes and procedures aimed at improving, developing and improving the available resources are valuable and beneficial to the academic community. Thus, the present research aims at the elaboration of a new composite material, using as raw material polyurethane (PU) wastes, rice husks and polyester resin, aiming to attribute to the material characteristics of thermal insulation. The rice husk is generated through the processing of the rice, in which it represents 20% of the mass of the grain. Its application in specific purposes are factors that have attracted the attention of researchers from several areas of knowledge. The PU is classified as a thermoset, so its recycling is not facilitated and can generate an environmental liability. The manufacture and consumption of PU has been increasing significantly in recent years worldwide, so waste generation is increased proportionally. Thus, it was proposed the manufacture of a composite from the union of these two wastes, generating a satisfactory material in terms of thermal insulation, but also viable and sustainable from the point of view of sustainability policies. The production of the composite was guided by the strategies of Cleaner Production (PML) and by the methodology Design Science Research (DSR). Three different compositions of the material were manufactured, varying the contents of each component. After the preparation, thermal conductivity tests were performed on the three types of composite, and it is possible to define the best formatting of the material with respect to thermal insulation. Secondary tests were performed in order to determine the hardness index of the material. As results, the coefficient of thermal conductivity was 0,06773 W / mK, hardness index of 82.92 HA and density of 580 kg/m³. In volume proportions, the material was composed of 50,33% PU, 42,77% rice husk and 6,90% polyester resin. These results indicate a satisfactory performance of the material as a thermal insulation, but its fragility can be considered as a negative aspect, being one of the limitations of its application. Finally, a technical analysis was carried out, evaluating factors such as the nature of the manufacturing process, the characteristics of the raw material and the mechanical properties of the material developed. In the cost measurement, the costs of implementation of the manufacturing process and costs of obtaining raw material were observed. In the environmental evaluation were pointed the factors of generation of wastes coming from each stage of the manufacturing process.